2014
DOI: 10.1038/hdy.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Farmers without borders—genetic structuring in century old barley (Hordeum vulgare)

Abstract: The geographic distribution of genetic diversity can reveal the evolutionary history of a species. For crop plants, phylogeographic patterns also indicate how seed has been exchanged and spread in agrarian communities. Such patterns are, however, easily blurred by the intense seed trade, plant improvement and even genebank conservation during the twentieth century, and discerning fine-scale phylogeographic patterns is thus particularly challenging. Using historical crop specimens, these problems are circumvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 62 publications
4
56
0
Order By: Relevance
“…About 90% of the landraces constituted the Cluster I and were from three bordering zones of Gojam namely: West Gojam, Awi, and Bahir Dar Zuria. This result indicates that there might have been exchange of seeds, and seed trade between farmers, and gene flow across boundaries of those areas (Forsberg et al, 2015). On the other hand, accessions from non-bordering origins were entirely constituted by a particular cluster such as landraces from South Gondar and East Gojam constituent cluster IV, and those from North Gondar and North Omo form cluster VIII.…”
Section: Discussionmentioning
confidence: 88%
“…About 90% of the landraces constituted the Cluster I and were from three bordering zones of Gojam namely: West Gojam, Awi, and Bahir Dar Zuria. This result indicates that there might have been exchange of seeds, and seed trade between farmers, and gene flow across boundaries of those areas (Forsberg et al, 2015). On the other hand, accessions from non-bordering origins were entirely constituted by a particular cluster such as landraces from South Gondar and East Gojam constituent cluster IV, and those from North Gondar and North Omo form cluster VIII.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that both the barley and rye grown in this region are genetically distinct from the ones grown in southern and central Europe (Jones, et al, 2011;Hagenblad, et al, 2016). For barley, it has been shown that these structures were present already in late 19 th century (Aslan, et al, 2015;Forsberg, et al, 2015) but the time-depth of these structures beyond that has remained unknown. One of the limiting factors has been the lack of suitable historical plant materials available for genetic analysis.…”
Section: Resultsmentioning
confidence: 97%
“…Improvement effects resulted from selection and breeding using only a small number of plants with the desired traits, followed by seed marketing and distribution over large areas outside of the region and traditions in which the original landraces formed (Jones, et al, 2008b). Studies based on landrace materials have, for example, been used to examine local adaptation to climate (Jones, et al, 2008a;Jones, et al, 2011;Aslan, et al, 2015) and population structures in order to determine the origins and spread of different crops on local scale (Pecetti and Damania, 1996;Papa, et al, 1998;Leino, et al, 2013;Forsberg, et al, 2015) or over larger distances (Hunt, et al, 2011;Jones, et al, 2011;Oliveira, et al, 2012a).…”
Section: Landracesmentioning
confidence: 99%
“…Genetic analysis of unimproved domesticated cultivars, known as landraces, of rye preserved in genebanks has shown much more variation within the landraces than among them (Persson and von Bothmer 2002;Hagenblad et al 2016). Compared to Fennoscandian landrace barley (Forsberg et al 2015) rye from this region shows little differentiation between landraces from different geographic areas. It has been suggested that when a wind pollinated, outbreeding crop such as rye is grown to the extent it has been cultivated in Fennoscandia, gene flow between fields and areas has been sufficient to homogenize the genetic diversity (Hagenblad et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…The distribution of genetic diversity in landraces may be seen as historical records of former trade routes and social interactions (Jones et al 2008;Forsberg et al 2015). In the sixteenth and seventeenth century the government supported migration of farmers from Finland to scarcely populated forest areas in the middle of Sweden, known to this day as Finnmarken (Myrdal and Söderberg 1991).…”
Section: Introductionmentioning
confidence: 99%